Contrast enhanced magnetic resonance imaging for uterine artery embolization efficiency assessment in women with leiomyoma uteri - Ye. A. Pavlovskaya; Ye. A. Yukhno; V. V. Ryazanov; I. A. Trofimenko; S. A. Sosin; S. V. Serebryakova (Опухоли женской репродуктивной системы)
Uterine artery embolization (UAE) is minimally invasive, less complicated and uterine-preserve procedure when compared to traditional surgical options. Magnetic resonance imaging (MRI) is the preferred modality in gynecologic pathology visualization. MRI is more accurate than transvaginal ultrasound in evaluating number, size and structure of the fibroids as well as their vascularization (by means of contrast enhancement) on pre-UAE uterus. On post-UAE contrast enhanced MRI, performed in 1, 6 and 12 month after the procedure, shrinkage of fibroids as well as the absence of their enhancement can be registered, showing the success or the manipulation. In case when leiomyoma is accompanied with adenomyosis, poor response of UAE can be noted by means of enhanced MRI revealing revascularization of fibroids. Thus, enhanced MRI is essential in UAE efficiency assessment, predicting treatment response and it’s complications.